Deep Brain Stimulation as a Treatment Approach for Anorexia Nervosa: a Systematic Literature Review - Silva, Ledismar José da; Naciff, Tâmara Husein; Oliveira, Maria Flávia Vaz de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Anorexia nervosa is a psychiatric disorder characterized by distortions of body size, weight, and shape perception, as well as by food restriction and/or binge and purging behaviors. It mostly affects young women and causes severe negative impacts on their physical, psychological, and social health. Recent studies have analyzed deep brain stimulation (DBS), a neurosurgical procedure that involves electrode implantation in strategical brain areas, to obtain remission of the symptoms of anorexia nervosa. The results showed that the stimulation of areas associated to the neurocircuitry of anorexia nervosa, such as nucleus accumbens, anterior cingulate cortex, ventral striatum, and bed nucleus of the stria terminalis, provokes beneficial responses in terms of body mass index, quality of life, social functioning, and psychiatric comorbidities. Nevertheless, broader investigations are needed to endorse the clinical usage of DBS in the management of anorexia nervosa.
Keywords: anorexia nervosa; eating disorder; deep brain stimulation; neuromodulation